WONDERSHARE QUIZ CREATOR SOFTWARE IMPROVES STUDENTS’ READING COMPREHENSION - Sangkala, Ismail; ul Haq, Muhammad Zia (Fakultas Keguruan dan Ilmu Pendidikan, 2014)
This research aimed at finding out whether or not the use of “Wondershare Quiz Creator Software” significantly improves the students’ reading comprehension of the English Education Program Class E and G, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar Academic Year 2012/2013, based on the narrative text was applied in reading material and investigating students’ interest in learning of reading through Wondershare Quiz Creator Software. The research employed the true experimental method. This research assigned two groups namely experimental group and control group. Each group consisted of 45 students. The sample was chosen by applying cluster random sampling technique. The researcher used reading test both in control and experimental group. The data obtained through the test were analyzed by using descriptive and inferential statistics through SPSS 16.0 version. In conducting the research, the researcher applied the “Wondershare Quiz Creator Software”. The research result showed that there was an improvement in the students’ reading comprehension between pretest and post-test in experimental group after the treatment. It was proven by the result of descriptive and inferential statistics in testing the students’ score either in pretest or in the posttest. The result of the data analysis showed that there was a significant difference between the result of posttest of experimental and control group, where the mean score of posttest of the experimental group was 82.22 which is higher than the mean score of posttest of the control group was 72.07. The research also showed that there was interested in the students on learning reading comprehension by using “Wondershare Quiz Creator Software”. It was proven by the result of the mean score of students’ Interest was 86.53 from the total respondent was 45 respondents. Hence, it is worthwhile concluded that “Wondershare Quiz Creator Software” significantly improved the students’ reading comprehension and students are interested in “Wondershare Quiz Creator Software”.